La Poésie de la resistance: (Louis Aragon, Gabriel Audisio, Jean Cassou, René Char, Paul Eluard, Pierre Émmanuel) - Betts, Madeleine (University of Ottawa (Canada), 1963)
Abstract not available.
Keywords: Literature, Romance.